Direct Artistic Restoration of Chewing Teeth - Asrorovna, Kholboeva Nasiba; Sobirovich, Khudaykulov Sardor (American Journal of Bioscience and Clinical Integrity, 2024)
The article is about artistic tooth restoration. It details methods for restoring tooth shape and color, including direct and indirect restorations. The article provides information on the benefits of tooth restoration as well as the materials used for tooth restoration. What is dental restoration? Artistic tooth restoration is a process that is performed to solve problems such as enamel discoloration, tooth shape or size, and tooth restoration after diseases such as caries or pulpitis.